Probiotics Supplementation Alleviates Endotoxemia-induced Behavioral Deficits in Mice (Asian Journal of Pharmaceutics (AJP), 2024)
Objective: The gut microbiota plays a critical role in maintaining normal mental health. Studies have highlightedthe role of probiotics in monitoring the bacterial population and modulating the gut-brain axis. Probioticsupplementation has received considerable attention as a potential therapeutic regime for the treatment ofbehavioral abnormalities. The present study elucidated the modulatory role of probiotics alone or as adjuncts withan agonist of the antipsychotic peptide neurotensin (NTS1) on behavioral deficits induced by endotoxin, bacteriallipopolysaccharide (LPS). Materials and Methods: Five groups of mice were maintained: control, LPS, LPS+ probiotics (Pro), LPS + NTS agonist (PD), and LPS + pro + PD. Mice were challenged with LPS (1 mg/kgbw) for 5 days, followed by supplementation of probiotics (0.6 g/kg bw), PD (50 μg/kg bw), and a combinationof pro and PD for 4 weeks. Results: LPS-exposed mice showed sickness behavior (decrease in food and waterintake), anxiety behavior (reduction in time duration, entries in the central square in the open-filed arena, andentries in the open arm in the elevated plus maze), and depressive behavior (increment in immobility time inthe force swimming test). A significant reduction in sickness, anxiety, and depressive behaviors as compared totheir LPS counterparts on supplementation of probiotics alone or in combination withNTS1 agonist; the efficacywas enhanced in the latter. Probiotics supplementation alone or in combination with NTS1 agonist, reduced theplasma levels of tumor necrosis factor-α, interleukin-6 (IL-6), and corticosterone, and increased plasma levels ofIL-10 might be due to increased beneficial bacteria Bifidobacteria and a decreased population of harmful bacteriaClostridia. Conclusion: Probiotic supplementation has the potential to prevent behavioral abnormalities, restorethe homeostasis of the microbiota, and may be used as a therapeutics adjunct along with other anti-psychotic drugsfor mental illness.